The Identification of Placental Alpha Micro Globulin-1 (Amnisure®) as a Method to Identify Rupture of Membrane - Jimmy P. Wirawan (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: We aimed to do a study in the use of the identification of Placental Alpha Micro Globulin-1 or PAMG-1, in the form of Amnisure ® test, as a method to diagnose rupture of membrane (ROM), compared with other conventional method (direct visualization and nitrazine test). Method: We used a cross-sectional design. Every pregnant woman who came to our hospital with gestational age of 14 to 42 weeks complaining of membrane rupture was recruited. Sterile speculum examination and nitrazine test was performed for every patient. Amnisure ® was utilized, using vaginal swab from posterior fornices. Data analysis was performed with SPSS version 17. Results: We recruited 20 patients to join our study. Mean age, parity and gestational age was 28.5 years, parity one and 35.5 ± 3.4 weeks of gestation. Amnisure® test was positive in 14 patients. With nitrazine as standard for ROM diagnosis, the sensitivity for Amnisure® was 85% and the specificity was 83.3%. The positive predictive value was 92.3% and negative predictive value was 71.4%. Conclusion: For every positive vaginal pooling, nitrazine and Amnisure ® will be tested positive. Several studies using Amnisure® have shown similar results. Role of Amnisure® seemed evident in cases of uncertainty such as chronic ROM and severe oligohydramnios due to ROM. Positive results in presence of intact membranes which suggested micro-perforations of the membrane still need further research. Much still needed to be done before implementing Amnisure® in our country, especially in the matter of cost effectiveness. [Indones J Obstet Gynecol 2012; 36-1:20-3] Keywords: amnisure®, PAMG-1, ROM